Abnormal cytoplasmic extensions associated with active αIIbβ3 are probably the cause for macrothrombocytopenia in Glanzmann thrombasthenia-like syndrome. Issue 3 (April 2015) - Hauschner, Hagit; Mor-Cohen, Ronit; Messineo, Stefania; Mansour, Wissam; Seligsohn, Uri; Savoia, Anna; Rosenberg, Nurit
<x xml:space="preserve">Abstract</x> Mutations in the ITGA2B or ITGB3 genes that encode for the αIIbβ3 platelet integrin usually cause Glanzmann thrombasthenia, a severe autosomal recessive bleeding disorder characterized by absence of platelet aggregation, but normal platelet number and size. Several rare mutations cause a Glanzmann-like syndrome which manifests macrothrombocytopenia and usually displays autosomal dominant inheritance. The exact mechanism causing Glanzmann-like syndrome is unknown. One typical example of Glanzmann-like mutations causes deletion of 40 amino acids (p.647–686) in the β3 β-tail domain (βTD_del) that was found in the heterozygous state in Italian and Japanese families. A second example is a missense mutation, C560R, located in the epidermal growth factor-like domain, found in the homozygous state in a French patient. Both mutations cause constitutive activation of αIIbβ3, but differ in their surface expression. In the current study, we generated cultured cells expressing β3-βTD_del or β3-C560R mutations along with wild-type αIIb, and examined the cells' ability to create tubulin-dependent protrusions compared to cells expressing wild-type αIIbβ3. Unlike cells expressing wild-type αIIbβ3, cells harboring each of the mutations exhibited abnormal cytoplasmic extensions on immobilized fibrinogen or Von Willebrand factor, which resembled extensions formed in megakaryocyte leading to proplatelets. Moreover, we showed that formation of abnormal extensions occurred also in wild-type αIIbβ3 cells when activated by activating antibody. These results suggest that the active conformation of αIIbβ3 can induce cytoskeletal rearrangements that lead to impaired proplatelet formation.